2020
DOI: 10.21203/rs.3.rs-17966/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FOXM1  modulates docetaxel resistance in prostate cancer by regulating KIF20A

Abstract: Background:Resistance to docetaxel is an important factor which affects the prognosis in advanced prostate cancer (PCa). The precise mechanisms remain unclear. The transcription factor Forkhead box M1 (FOXM1), participating in cell cycle progress and cell proliferation, has been reported to affect the sensitivity of chemotherapy. The present study aims to explore the role of FOXM1 in docetaxel resistance of PCa and how FOXM1 is associated with kinesin family member 20 A (KIF20A), which has been demonstrated to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Some researchers reported that TOP2A could induce apoptosis and suppress cell growth and invasion via AKT/ERK signaling pathways in colon cancer [7]. Kinesin family member 20A (KIF20A) is believed to modulate microtubule dynamics [60], which could promote the tumorigenesis and progression of prostate cancer and glioma [61], particularly the biochemical recurrence and metastasis [60,62]. Silencing KIF20A could induce prostate cancer cells to death and aberrantly activated Gli2-KIF20A axis which is crucial for the growth of hepatocellular carcinoma and predicts poor prognosis in hepatocellular carcinoma [63].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported that TOP2A could induce apoptosis and suppress cell growth and invasion via AKT/ERK signaling pathways in colon cancer [7]. Kinesin family member 20A (KIF20A) is believed to modulate microtubule dynamics [60], which could promote the tumorigenesis and progression of prostate cancer and glioma [61], particularly the biochemical recurrence and metastasis [60,62]. Silencing KIF20A could induce prostate cancer cells to death and aberrantly activated Gli2-KIF20A axis which is crucial for the growth of hepatocellular carcinoma and predicts poor prognosis in hepatocellular carcinoma [63].…”
Section: Discussionmentioning
confidence: 99%